The Influence Of Work Values And Adversity Quotient On Employee Performance Through Affective Commitment And Affiliation Motivation (A Study On Millennial Employees At BNI KCU Perguruan Tinggi Bandung) - Saputra, Raden Muhammad Iqbal Rizqi; Muhyi, Herwan Abdul; Dai, Ratna Meisa (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to analyze the influence of work values and adversity quotient on employee performance, with affective commitment and affiliation motivation as mediating variables, focusing on millennial employees at BNI KCU Perguruan Tinggi Bandung. A quantitative approach was employed using a survey method involving 101 respondents selected through simple random sampling. The research instruments were adapted from established theories and analyzed using PLS-SEM with SmartPLS software. The results indicate that work values have a significant direct effect on employee performance, and an indirect effect through affiliation motivation. Adversity quotient does not directly influence performance significantly, but has a strong indirect effect through affiliation motivation. Affective commitment showed a marginal mediating effect. These findings highlight the importance of affiliation motivation in enhancing the performance of millennial employees and the need for organizations to foster a workplace environment that supports social relationships and aligns with the work values of this generation.